A single wire as all-inclusive fully functional supercapacitor. (February 2017) - Kang, Qi; Zhao, Jin; Li, Xue; Zhu, Guoyin; Feng, Xiaomiao; Ma, Yanwen; Huang, Wei; Liu, Jie
Abstract: A key challenge in wire-shaped energy storage devices is their complete encapsulation for practical applications. Hence it is of great importance to design and fabricate an all-inclusive structure in which inner and outer current collectors, active materials, electrolyte and separator are all enclosed in a single wire structure. However, due to the surface area differences between the shell and core electrodes, the matching of the capacitance on both electrodes become a challenging task. We solved this problem by using multiple thin Ni wires with three-dimensional MnO2 -carbon nanotubes (CNTs)-graphene hybrids as the core electrode and a Ni tube as the shell electrode in a coaxial-cable supercapacitors structure. Within the seamless tubular electrode, all the necessary components are included and protected by the metal tube shell. The fully encapsulated single wire devices show a high area-normalized capacitance of 31 mF cm −2 at a current density of 0.29 mA cm −2, comparable to the best cable devices with more exposed structures. Such devices are more suitable for applications by providing more mechanical stability and avoiding exposure and loss of electrolytes during operation. Graphical abstract: Highlights: An approach to solve the matching of the capacitance between the shell and core electrodes is proposed by using multiple thin wire core electrode to fit a tubular shell electrode. The fully encapsulated single wire devices show a high area-normalized capacitance, comparable to the best cable devices with more exposed structures.